The application of blended learning in obstetrics teaching: a comprehensive teaching model integrating an intelligent, interactive induction platform - Gu, Kaifen; Pan, Haiyan; Dong, Meiyuan; Chen, Xuanjin; Yuan, Huiping (Frontiers in Medicine, 2025)
IntroductionHybrid learning, integrating diverse teaching methods and resources, is promising in education. In nursing, it suits varied learning styles via multiple channels and offers time-place flexibility, aiding busy practice nurses. Information and Communication Technology (ICT) is vital in modern nursing education. Medical intelligent induction platforms, as its form, simulate real-life scenarios for safe skill practice and provide real-time feedback for learning enhancement.ObjectiveThis study aimed to evaluate impact of blended learning in obstetrics teaching using a medical intelligent induction interactive platform on multiple dimensions. These dimensions include the scores of theoretical teaching and practical operation, independent learning ability, comprehensive ability, and overall nursing quality.MethodsFrom August 2022 to August 2023, 70 practice nurses in our hospital were selected, and they were divided into the control group and the research group. The control group received training and teaching through conventional methods. The research group adopted a blended learning model using the medical intelligent induction interactive platform.ResultsThe research group outperformed the control group significantly (P < 0.05) in theoretical teaching performance, practical operation performance, independent learning ability, comprehensive ability, and overall nursing quality. Moreover, the 35 trainee nurses in the research group showed relatively high overall satisfaction with the blended learning model combined with the medical intelligent guidance interactive platform.ConclusionIntegrating the blended learning method with the medical intelligent induction interactive platform for teaching clinical intern nurses can significantly enhance their relevant nursing knowledge, practical operation skills, and autonomous learning ability, thereby elevating the quality of nursing.